2021
DOI: 10.1094/phyto-06-20-0215-r
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Cassava Planting Material Movement and Grower Behavior in Zambia: Implications for the Management of Cassava Virus Diseases

Abstract: Cassava is an important food crop across sub-Saharan Africa, where production is severely inhibited by two viral diseases; cassava mosaic disease (CMD) and cassava brown streak disease (CBSD), both propagated by a whitefly vector and via human-mediated movement of infected cassava stems. There is limited information on growers’ behaviour related to movement of planting material, as well as growers’ perception and awareness of cassava diseases, despite the importance of these factors for disease control. This s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Although tolerance and resistance to disease have been widely researched in plant biology, little thought has been given to the distinct epidemiological consequences of deploying tolerant or resistant varieties upon a community of growers, and none to how this affects the decisions of growers to partake in control. Growers’ behaviour more broadly, and its effects on epidemic outcomes remains largely overlooked in plant disease epidemiology (with some exceptions including [3033,5961]). Here, we investigated the effect of a fixed proportion of ‘improved’ crop (with either tolerant or resistant characteristics) on growers’ profits and subsequently how this affected growers’ use of improved crop when given the choice.…”
Section: Discussionmentioning
confidence: 99%
“…Although tolerance and resistance to disease have been widely researched in plant biology, little thought has been given to the distinct epidemiological consequences of deploying tolerant or resistant varieties upon a community of growers, and none to how this affects the decisions of growers to partake in control. Growers’ behaviour more broadly, and its effects on epidemic outcomes remains largely overlooked in plant disease epidemiology (with some exceptions including [3033,5961]). Here, we investigated the effect of a fixed proportion of ‘improved’ crop (with either tolerant or resistant characteristics) on growers’ profits and subsequently how this affected growers’ use of improved crop when given the choice.…”
Section: Discussionmentioning
confidence: 99%
“…Such involvement is necessary to improve cooperation and coordination amongst participants (Sherman et al 2019) and should form part of any risk-based approach to disease management (Hyatt-Twynam et al 2017). These concerns were mirrored in studies on Clas in California (Garcia-Figuera et al, 2021), cassava mosaic virus disease in Zambia (Szyniszewska et al 2021) (Electronic Supporting Information, S5). Other studies on disease management of Clas have given detailed accounts of control techniques such as precision trunk inoculation but have not considered the implications for all participants (Li and Nangong, 2021: Electronic Supporting Information, S5).…”
Section: Implications For Disease Managementmentioning
confidence: 95%
“…Prior to first report of CMD outbreak in Cambodia, a study conducted in 2016-2017 on the movement and exchange of cassava planting materials in Cambodia and Vietnam within communes found 82 and 78% of seed provided to others being exchanged between family and acquaintances, respectively (Delaquis et al, 2018). Similarly, in some African countries including Zambia were cassava is mostly grown by small scale farmers, frequent seed exchange occurs between farmers (94%) in the same or nearby communities (Szyniszewska et al, 2021). A similar study in Rwanda indicated that majority (76.9%) of the farmers obtain cuttings for free from either their own fields or from neighbors (Nyirakanani et al, 2021).…”
Section: Seed Systems and Disease-free Planting Materialsmentioning
confidence: 99%
“…Cassava seed systems in Africa are largely farmer driven with low seed quality controls. Re-use of the farmer's own seed supply remains the most common source of seed (Kidasi et al, 2021;Szyniszewska et al, 2021).…”
Section: Seed Systems and Disease-free Planting Materialsmentioning
confidence: 99%